2017
DOI: 10.1038/s41598-017-00130-x
|View full text |Cite
|
Sign up to set email alerts
|

Lack of XPC leads to a shift between respiratory complexes I and II but sensitizes cells to mitochondrial stress

Abstract: Genomic instability drives tumorigenesis and DNA repair defects are associated with elevated cancer. Metabolic alterations are also observed during tumorigenesis, although a causal relationship between these has not been clearly established. Xeroderma pigmentosum (XP) is a DNA repair disease characterized by early cancer. Cells with reduced expression of the XPC protein display a metabolic shift from OXPHOS to glycolysis, which was linked to accumulation of nuclear DNA damage and oxidants generation via NOX-1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 62 publications
(84 reference statements)
1
15
0
Order By: Relevance
“…Evidence of mitochondrial dysfunction in XP has been indicated by mitochondrial DNA (mtDNA) deletions [ 150 , 151 ], ETC enzyme dysfunction [ 147 , 152 ] and morphological abnormalities [ 153 , 154 ]. Interestingly, studies have suggested that mitochondria are the major source of ROS generation in human XP-C cells and that mtDNA is the primary target for damage accumulation [ 152 ]. Since mtDNA lacks an NER, with repair being elicited through other mechanisms [ 155 ], this does suggest that mitochondrial abnormalities reported in XP are a secondary consequence of abnormalities in the nuclear DNA repair system.…”
Section: Xeroderma Pigmentosummentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence of mitochondrial dysfunction in XP has been indicated by mitochondrial DNA (mtDNA) deletions [ 150 , 151 ], ETC enzyme dysfunction [ 147 , 152 ] and morphological abnormalities [ 153 , 154 ]. Interestingly, studies have suggested that mitochondria are the major source of ROS generation in human XP-C cells and that mtDNA is the primary target for damage accumulation [ 152 ]. Since mtDNA lacks an NER, with repair being elicited through other mechanisms [ 155 ], this does suggest that mitochondrial abnormalities reported in XP are a secondary consequence of abnormalities in the nuclear DNA repair system.…”
Section: Xeroderma Pigmentosummentioning
confidence: 99%
“…Decreased activities of the antioxidant enzymes, catalase [ 156 ], SOD (superoxide dismutase) [ 143 ] and GSH-PX [ 152 ] have been reported in patient tissue and cell models of XP. In addition, decreased plasma CoQ 10 levels were reported in patients with XP, with improvements in their daily activity being documented in a subset of these patients following CoQ 10 supplementation [ 157 ].…”
Section: Xeroderma Pigmentosummentioning
confidence: 99%
“…In locus correction of XPC defect with WT XPC reverted all bioenergetics parameters, but not mtDNA damage and deletion. Finally, the XPC‐associated imbalanced CI/CII activity led to increased sensitivity of XP‐C cells to mitochondrial oxidative stress, which was completely corrected by WT XPC expression (Mori et al, ).…”
Section: Disorders Of the Nucleotide Excision Repairmentioning
confidence: 99%
“…We have recently reported that XP-C cells display a shift between respiratory complexes I and II utilization, accompanied with increased mitochondrial H 2 O 2 production and decreased GPx activity (Mori et al, 2017). Moreover, this shift between complex I and II resulted in an increased cellular sensitivity to mitochondrially induced redox unbalance that was fully reverted in an isogenic corrected XP-C cell line.…”
Section: Introductionmentioning
confidence: 97%